Liquid‐Based Exfoliation of Black Phosphorus into Phosphorene and Its Application for Energy Storage Devices. Issue 5 (11th May 2021) - Rabiei Baboukani, Amin; Khakpour, Iman; Drozd, Vadym; Wang, Chunlei
Abstract : Energy Storage Devices In article number 2000148, Amin Rabiei Baboukani, Chunlei Wang, and co‐workers summarize the fundamentals and latest advances in liquid‐based exfoliation of black phosphorus into phosphorene nanosheet and its application for rechargeable batteries and supercapacitors. Effects of exfoliation parameters through sonication, electrochemical, and bipolar exfoliation are systematically discussed. This work inspires efforts to further investigate phosphorene nanosheets for advanced energy storage devices.